La diversidad de género en la alta dirección de las mayores empresas espa\~nolas - P. de Luis Carnicer; Angel Martínez Sánchez; Manuela Pérez Pérez; M. J. Vela Jiménez (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2007)
This paper analyses the relationship between firm performance and women on boards and top management positions in a sample of large Spanish firms in the period 2000-2004. The results of the study indicate that the percentage of women on boards and top management teams is much lower in industrial and technological sectors than in services. The participation of women is greater in industries that have greater percentages of women in the workforce. The relationship between women participation on boards and firm performance depend on the measure of female representation and the measure of firm performance. The variation of firm performance in the period 2000-2004 does not explain the variation of female representation on boards and top management during that period.
Keywords: 330; corporate governance; women; firm performance